2014
DOI: 10.1371/journal.pone.0098560
|View full text |Cite|
|
Sign up to set email alerts
|

Sinomenine Sensitizes Multidrug-Resistant Colon Cancer Cells (Caco-2) to Doxorubicin by Downregulation of MDR-1 Expression

Abstract: Chemoresistance in multidrug-resistant (MDR) cells over expressing P-glycoprotein (P-gp) encoded by the MDR1 gene, is a major obstacle to successful chemotherapy for colorectal cancer. Previous studies have indicated that sinomenine can enhance the absorption of various P-gp substrates. In the present study, we investigated the effect of sinomenine on the chemoresistance in colon cancer cells and explored the underlying mechanism. We developed multidrug-resistant Caco-2 (MDR-Caco-2) cells by exposure of Caco-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Li et al reported that sinomenine induces breast cancer cell death via MAPK signal pathway and reactive oxygen species (ROS) generation (15). Combined chemotherapy with senomenine treatment (25)(26)(27)(28) has been revealed to sensitize multidrug-resistant cancer cells in various cancers. Song et al demonstrated that sinomenine inhibited invasion and migration in breast cancer by suppressing NF-κB activation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that sinomenine induces breast cancer cell death via MAPK signal pathway and reactive oxygen species (ROS) generation (15). Combined chemotherapy with senomenine treatment (25)(26)(27)(28) has been revealed to sensitize multidrug-resistant cancer cells in various cancers. Song et al demonstrated that sinomenine inhibited invasion and migration in breast cancer by suppressing NF-κB activation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that celecoxib may prevent chemotherapy drug resistance in digestive and gynecologic carcinomas (9)(10)(11)(12), but whether it serves a similar role in T-cell lymphoma has not been determined. The present study demonstrated that celecoxib sensitized Jurkat and Hut-78 cells to various chemotherapy drugs by triggering apoptosis and inhibiting the expression of MDR-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…P65, the primary functioning subunit of activated NF-κB, is an important indicator for predicting MDR in tumors, as it promotes cell viability, causes apoptosis resistance and enhances expression of various MDR-associated proteins including P-gp and MRP1 (7). Furthermore, previous studies have also confirmed that the expression of Bcl-2 may be directly upregulated by activation of the NF-κB signaling pathway, thereby inhibiting Bax expression and leading to an anti-apoptotic effect in tumor cells (8)(9)(10)(11). In the present study, the results suggested that the expression of P65, Bcl2, P-gp and MRP1 was significantly decreased, while the expression of Bax was increased in celecoxib-treated Jurkat and Hut-78 cells t compared with those that were not treated with celecoxib.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Studies have showed that, inhibition of multidrug resistance (MDR) ability of resistant cancer cells would be a good way to achieve successful cancer therapy and to decrease the dose of anticancer drugs. [3][4] In order to reduce the clinical-used drug dosage and side-effects, drug-delivery systems (DDS) have been developed to overcome this problem,because they offered excellent efficient drug transportation.…”
Section: Introductionmentioning
confidence: 99%